Abrupt spin transition in a modified-terpyridine cobalt(ii) complex with a highly-distorted [CoN6] core. Issue 39 (15th August 2018) - Nakaya, Manabu; Ohtani, Ryo; Shin, Jong Won; Nakamura, Masaaki; Lindoy, Leonard F.; Hayami, Shinya
Abstract : The cobalt(ii ) complex [Co(Naph-C2-terpy)2 ](BF2 )2 (1 ) incorporating a highly distorted [CoN6 ] core was found to exhibit abrupt spin transition behavior, unlike solvated1 ·2MeOH, which showed gradual spin crossover behavior. Abstract : The cobalt(ii ) complex incorporating π-conjugated substituent, [Co(Naph-C2-terpy)2 ](BF4 )2 (1 ; Naph-C2-terpy = 4′-(2-naphthoxy(ethoxy))-2, 2′:6′, 2′′-terpyridine), exhibits an abrupt spin transition (ST) behavior (cooperative factor C = 0.91) while its solvated product, 1 ·2MeOH, shows gradual spin crossover (SCO) behavior ( C = 0.49). Single crystal X-ray structural analyses demonstrated that the octahedral coordination core [CoN6 ] in1 shows larger distortion in both high-spin and low-spin states than solvated1 ·2MeOH or another two derivatives, [Co(R-terpy)2 ](BF4 )2 (R = 2-naphthyl (2 ), 9-anthracenyl (3 )). The respective distortion parameters ( Σ ) are compared with those for previously reported SCO cobalt(ii ) compounds. The highly-distorted [CoN6 ] core in1 ( Σ = 126 in the HS state and 101.6 in the LS state) was stabilized by strong intermolecular interactions and observed an abrupt ST behaviour.